MODERN POLLEN AND STOMATE DEPOSITION IN LAKE SURFACE SEDIMENTS FROM ACROSS THE TREELINE ON THE KOLA PENINSULA, RUSSIA - Gervais B.R.; MacDonald G.M. (My University, 2001)
We sampled and analyzed surface sediments from 31 lakes along a latitudinal transect crossing the coniferous treeline on the Kola Peninsula, Russia. The major vegetation zones along the transect were tundra, birch-forest tundra, pine-forest tundra, and forest. The results indicate that the major vegetation types in our study area have distinct pollen spectra. Sum-of-squares cluster analysis and principal components analysis (PCA) groupings of pollen sites correspond to the major vegetation zones. PCA ordination of taxa indicates that the first axis separates taxa typical of the forest zone (Pinus, Picea) from taxa typical of tundra and forest-tundra zones (Polypodiaceae, Ericaceae, and Betula). The current position of the coniferous treeline, defined in our region by Pinus sylvestris, occurs roughly where Pinus pollen values reach 35% or greater. Arboreal pollen (AP)/non-arboreal pollen (NAP) ratios were calculated for each site and plotted against geographic distance along the transect. AP/NAP ratios of 7 or greater are found within pine-forest tundra and forest vegetation zones. Pinus stomates (dispersed stomatal guard cells) are absent from sites north of the coniferous treeline and all but two samples from the forested sites contain stomates. Stomate concentrations among the samples are highly variable and range from 10 to 458 per ml and positively correlate with the changing Pinus pollen values.